An Assessment of the Authorization to Sell Veterinary Pharmaceuticals in terms of the Veterinary Profession: II. Effects of the Authorization to Sell Pharmaceuticals on Vision and Balance Sheet - Ozen, Abdullah; Yuksel, Erhan; Dogan, Ozlem (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
The present study was conducted to determine the effects of the authorization to sell veterinary pharmaceuticals on the balance sheet of veterinary clinics and the vision of private veterinary practitioners. For this purpose, data was collected from 400 private veterinary practitioners by means of a questionnaire. The frequency analysis and calculation of arithmetical means revealed that private veterinary practitioners working at clinics specialized in farm animals showed a tendency to abandon symbols specific to the veterinary profession, including lab coats and prescriptions. Although the number of registered patients, number of clients with a demand for clinical services, number of clients with a demand for all veterinary medical services, number of clients with the sole demand of buying pharmaceuticals and the proportion of the sales turnover to the global turnover of farm animal clinics were higher than those of pet clinics, the values pertaining to the pet clinics for the average contribution of patient/client numbers to the monthly turnover were higher than those of farm animal clinics.
Veteriner İlaçları satış yetkisinin veteriner hekimli?i açısından de?erlendirilmesi: II. İlaç satış yetkisinin vizyon ve bilanço üzerine etkileri
Keywords: Veterinary profession; Veterinary clinics; Sales of pharmaceuticals; Vision; Balance sheet